Uso da restrição alimentar quantitativa para diminuir a mortalidade de frangos de corte machos - Gonzales, Elisabeth [UNESP]; Junqueira, Otto Mack [UNESP]; Macari, Marcos [UNESP]; Andreatti Filho, Raphael Lucio [UNESP]; Garcia, Edivaldo Antonio [UNESP] (My University, 1998)
The effect of feed restriction (0, 10, 20, 30, 40 and 50%) from 8 until 14 days post-hatching on performance, total mortality incidence and sudden death syndrome (SDS) rate was studied in male broilers during winter and summer.Ad libitum fed broilers had a better performance, but a higher total mortality rate (13.00% in winter, 3.67% in summer) and SDS (3.67% in winter, 0.67% in summer). All restricted groups had a lower mortality level in winter than the control group with a non linear response influenced by feed restriction. Birds submitted to 40% feed restriction showed the lowest mortality incidence (2.67%) followed by groups submitted to 30% (4.67%), 50% (5.33%) and 10% and 20% (7.67%) feed restriction. Birds fed ad libitum had the highest SDS incidence (3.67%, against .33, 1.00, .67, 1.33 and 1.33% at 10, 20, 30, 40, 50% feed restriction, respectively), but differences were not significant. In summer, incidences of total mortality and due to SDS were low and not influenced by feed restriction, either during the restrictive period itself (8 to 14 days) or during the total period of raising (1 to 49 days). In both seasons, the feed restricted birds showed compensatory gain only until three weeks post-restriction period. At 49 days, body weight and weight-gain were lower in feed restricted birds, but feed :gain ratio rate was improved. This resulted in better productivity index in winter, but not in summer. The feed restriction at 30 to 40% for seven days during the second week may decrease mortality in male broilers raised in winter without lowering productivity if the restriction is followed by at least three weeks of full feeding.
Using quantitative feed restriction to decrease mortality of male broilers
Keywords: Broiler; Male; Mortality; Performance; Quantitative feed restriction; SDS; Sudden death syndrome; Summer; Winter; Aves